FAMILY EFFORTS IN LOOKING FOR MENTAL HEALTH SERVICES IN REMOTE AREA OF SANGIHE ISLANDS DISTRICT - Nansy Delia Pangandaheng (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2021)
Background: The problem of mental health services is inseparable from the reach of health services at hospitals or community health center including development in remote. The implementation of health services in remote areas, including the Sangihe Islands district, go through obstacles due to the difficulty of the terrain by frequently. The people have difficulty accessing health services due to the lack of transportation facilities and dependence on the season. The purpose: Elucidate the efforts of families in seeking mental health treatment in remote areas. The methods: This study uses a qualitative method of phenomenological approach, with purposive sampling technique. The informants in this study were seven families who cared for clients with mental disorders. The data analysis process was carried out using the Collaizi method which consists of seven stages. The validity of research data using triangulation methods with interviews, observation and triangulation among members of the researcher to avoid researcher subjectivity. In addition, researchers conducted member cheking, namely by validating data from informant interviews. Result: Four themes were found in this qualitative research, namely behavioral changes, sources of information on the availability of mental health services, treatment seeking behavior, barriers to looking for mental health services. Conclusion: Six families have taken clients to a neurologist, pastor, and psychiatric hospital, but there is a family who never received medical or traditional treatment because the client refused to be treated.